"Se a prova fosse sobre os rebeldes eu ia tirar 10": culturas visuais tramando masculinidades na escola - Nunes, Luciana Borre (2014)
Childhoods are social, cultural and historical constructions inserted in networks of power and representation processes. So, I dialogue with twenty children of the 3th year of an Elementary Public School (ages between 8 to 11 years old) in Goiânia, Goiás, searching to understand which representations of masculinity are circulating in school and how masculinities are constituted and mediated by images and cultural artifacts in a classroom. The main focuses of this research are: (1) to understand how children between 8 and 11 years old constitute their masculinities mediated by cultural elements in day-by-day experiences in the school; (2) to understand how do they express their representations of masculinity in school and; (3) to discuss how are produced pedagogical "weaves" for the constitution of gender and sexuality in the classroom. The investigation was driven by an ethnographic bias and the development of analyses, the contributions of Visual Culture Studies and Gender and Sexuality Studies were used, particularly those associated with the post-structuralism approaches. Focal groups, notes in a diary and the developing of a pedagogical action with photographs were used as strategies for data production. The results showed that there are a multiplicity of masculinities permeated by images and cultural artifacts that perform a kind of pedagogy in the classroom; heteronormative narratives that constitute a major source of learning about gender and sexuality in school reverberating in other areas; heterosexuality defended by some boys with acts of exclusion and ridicule of their classmates who do not meet hegemonic masculinity requirements; religious direction valued by the teachers and the school community as synonymous of discipline, norms of conduct, dissemination of good practices for school living, and also, as an attempt to fight violence; distance between school knowledge and childhood everyday knowledge and, as result, repudiation of images and cultural artifacts that are banned from the classroom and; cultural consumption as an important piece in the gearing of interpersonal relationships in the classroom.